2017
DOI: 10.4067/s0717-95022017000401224
|View full text |Cite
|
Sign up to set email alerts
|

Model Analysis of Anatomical Morphology Changes of Palatal Rugae Before and After Orthodontic Treatment

Abstract: LI, B.; TAE-GEON, K.; WU, X. ; HEE-MOON, K. ; KE-MING, Y. & XIU-PING, W.Model analysis of anatomical morphology changes of palatal rugae before and after orthodontic treatment. Int. J. Morphol., 35(4):1224Morphol., 35(4): -1229Morphol., 35(4): , 2017. SUMMARY:Model analysis was performed to identify palatal rugae anatomical morphology patterns, evaluate their individual-specific properties and stability before and after orthodontic treatments, and investigate their reliability in the use for individual identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Joanna Brigg’s risk of bias assessment: Out of 18 studies, 11 showed a moderate risk of bias [ 8 , 19 , 20 , 22 , 24 , 26 , 27 , 29 , 30 , 31 , 32 ] and 7 showed a low risk of bias [ 16 , 17 , 18 , 21 , 23 , 25 , 28 ] ( Table 2 ). Inclusion criteria have been properly defined by seven studies [ 17 , 18 , 21 , 23 , 25 , 28 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Joanna Brigg’s risk of bias assessment: Out of 18 studies, 11 showed a moderate risk of bias [ 8 , 19 , 20 , 22 , 24 , 26 , 27 , 29 , 30 , 31 , 32 ] and 7 showed a low risk of bias [ 16 , 17 , 18 , 21 , 23 , 25 , 28 ] ( Table 2 ). Inclusion criteria have been properly defined by seven studies [ 17 , 18 , 21 , 23 , 25 , 28 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Joanna Brigg’s risk of bias assessment: Out of 18 studies, 11 showed a moderate risk of bias [ 8 , 19 , 20 , 22 , 24 , 26 , 27 , 29 , 30 , 31 , 32 ] and 7 showed a low risk of bias [ 16 , 17 , 18 , 21 , 23 , 25 , 28 ] ( Table 2 ). Inclusion criteria have been properly defined by seven studies [ 17 , 18 , 21 , 23 , 25 , 28 , 32 ]. Details of the subjects included in the studies, objectives, and standard criteria used for the measurement and the reliability and validity of the exposure measurement tool have been described by thirteen studies [ 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Além desses supracitados, as pesquisas de Babaji et al (2018), Bing et al (2017a), Xiu-Ping et al (2017, Wu et al (2016), Muhasilovic et al (2016) e Lima et al (2016 também avaliaram os principais aspectos da análise de diferenciação de gênero pela rugoscopia palatina. Ademais, os autores estabeleceram a importância de tal método para a análise forense e a anuência de que não há influência no tratamento ortodôntico na observação de tais rugas (Wu et al, 2016;Xiu-Ping et al, 2017;Muhasilovic et al, 2016) e, além disso, o uso da tecnologia para o reconhecimento de tais diferenças morfológicas é fundamental para a identificação forense (Babaji et al, 2018;Bing et al, 2017b;Lima et al, 2016).…”
Section: Resultsunclassified